تحليل مفهوم الجاهلية في فكر سيد قطب = An analysis of the notion of “Jahiliyyah” in Sayyid Qutb’s discourse - El-Banna, Ibrahim Abdalla; Mohd Daud, Noor Amali (USIM Press, 2019)
تسعى هذه الدراسة إلى تحليل مفهوم "الجاهلية" في فكر سيد قطب، مع بيان الفرق بين المجتمع الإسلامي والمجتمع الجاهلي من وجهة نظره، مع طرح أهم الأسباب التي جعلت سيد قطب يضع المجتمعات في بوتقة الجاهلية، بالإضافة إلى تسليط الضوء على الآراء المؤيدة والمعارضة لمفهوم الجاهلية.وقد انتهجت الدراسة المنهج الكيفي وذلك بتحليل آراء سيد قطب حول الجاهلية من خلال كتاباته ومقارنتها مع آراء الباحثين الآخرين ونقدها وتأصيلها.خلصت الدراسة إلى أن الجاهلية عند سيد قطب هي حكم البشر للبشر، والخروج من عبودية الله، ورفض ألوهية الله، والاعتراف في مقابل هذا الرفض بألوهية بعض البشر، وبالعبودية لهم من دون الله، بالإضافة إلى أن الدراسة أفصحت من خلالها أن الجاهلية قد أتت في كثير من المواضع التي تحدث عنها "سيد قطب" بمعنى التخلف، والقيم، والسلوك، والفسق، والانحراف، وهذه الاستعمالات تستقيم مع المعني اللغوي للكلمة. ********************************************************** The study investigates the notion of “jahiliyya” according to Sayyid Qutb. It covers the discussion on the demarcation line between Islamic and jahiliyya societies and Qutb‟s justification of considering societies in general as under the shadow of Jahiliyyah. The study also analyses views from supporters of Qutb and also the opponents of his view in regards to the notion. Using qualitative methodological framework, the study characterizes, compares and appraises Qutb‟s views on „jahiliyyah‟ based on his writings and others. It can be concluded that „jahiliyyah‟ addressed by Qutb exemplifies the ideas of man‟s judgement over man in the one hand, and the non-acknowledgement of God‟s supremacy by giving a due recognition of man‟s lordship in the other. The study also summed up that jahiliyyah in Qutb‟s discourse predominantly carries the meaning of backwardness, certain values, attitudes and deviation. Those prescribed meanings are altogether in line with the literal sense of the word.